Visual and Verbal Ascribing of Meanings to the Term “Holy” in the German Magazines Stern and Spiegel - Stander-Dulisch, Judith (Journal of religion, media and digital culture, 2018)
The case study focuses on how the semantic field sacred is linguistically and visually taken up in the German weekly print magazines Stern and Spiegel. Both magazines are defined by the use of visual material. Therefore, the analysis is based on theoretical concepts of image linguistics, which deal with the effect and functions of the connection of language and image in mass media.